Civil Orders for Protection: Freedom or Entrapment? - Nina W. Tarr (Washington University Journal of Law & Policy, 2003)
Twenty years ago, we, as advocates, hoped that Orders for Protection would invoke the criminal justice system to protect victims of abuse, but now we see that relying on the legal system can make the life of abuse victims even more unmanageable. A woman who seeks an Order for Protection because she is being abused in either her home or partnership risks finding herself the “victim” of a host of Alice in Wonderland experiences that may result from the policies of mandatory arrests, “hard” no-drop policies, state child protective services, overcrowded courts, insurance discrimination, welfare benefit loss, employment discrimination, immigration policies, and “equality theory” child custody laws. This Essay describes some of the ways that the state now entraps battered women by the Order for Protection system so that lawyers and advocates will fully advise their clients of the consequence of their choices.
Keywords: Abused women; Civil procedure; Domestic violence; Orders (Law); United States